REGULARITIES OF CHANGE OF EFFICIENCY OF OIL WELLS OF THE FIELD OF VELICHAEVSKO-KOLODEZNE - Mikhail V. Nelepov; Tatyana V. Logvinova; Andrey A. Likhovid (Вестник Северо-Кавказского федерального университета)
In article comparison of various geological parameters of oil pools to level of production of hydrocarbons on wells is carried out. On the actual material extent of influence of various geological factors at sizes of efficiency of oil wells is estimated.